UPLC-MS/MS Based Identification of Dietary Steryl Glucosides by Investigation of Corresponding Free Sterols - Münger, Linda H.; Boulos, Samy; Nyström, Laura (Frontiers in Chemistry, 2018)
Dietary plant foods are characterized by a vast molecular diversity of glycosylated sterols (SG) that differ in the structure of the steryl backbone. The identification of these polar steryl conjugates represents a major challenge as they are structurally highly similar, and commercial standards are limited to a few naturally abundant species. Spectral databases do not yet contain MS/MS spectra of these sterols conjugates obtained by electrospray ionization (ESI), which would facilitate their reliable identification. Thus, this study aimed at providing novel information on ESI-MS/MS spectra of both abundant and minor SG found in foods. As a first step, however, free sterols (FS) were investigated for their fragmentation behavior as they share the same intermediate ion as SG. Pure SG were obtained from commercially available standard mixtures and minor SG were extracted from different food sources (oat bran, wheat bran, pumpkin seeds, melon, rapeseeds and potato peel). ESI-MS/MS spectra of 15 FS were assessed and fragment ions reflective of structural features were identified and rationalized. Subsequently, 14 SG were identified at four different levels, while relative retention times from chromatographic separation and spectral features of FS served to identify five SG. Spectral data from FS were directly transferable to SG when analyzed as aglycone ions as shown by similarity scores while SG were characterized by shorter retention times in reverse phase chromatography and the additional analysis as sodiated adduct confirmed their glycosidic nature. Moreover, we report for the first time the occurrence of 24 methylenecholesterol and a 4 monomethyl sterol as glycosidic conjugates in higher plants. The presented data will serve as a valuable tool for SG profiling of foods by facilitating their identification.